PENERAPAN PRINSIP KEHATI-HATIAN PADA PENYALURAN PEMBIAYAAN DI BAITUL MAAL WAT TAMWIL (BMT) Studi Analitis di BMT Daarut Tauhiid - Ahmad Rifai sanusi (iLearning Journal Center, 2019)
This study aims to determine the application of prudential principles in Baitul Maal Wat Tamwil (BMT). The case study was conducted on the distribution of funding in Baitul Maal Wat Tamwil (BMT) Daarut Tauhiid (DT) Bandung using data from January 2018 until Ocotober 2019. From research conducted by author in BMT Daarut Tauhiid, found that the principle of prudence on channeling of financing in BMT Daarut Tauhiid absolutely applied. This is realized in the form of adherence to the values ​​of sharia in financing. Such as the application of the contract principle in accordance with the contract of sale, the profit sharing agreement and the lease agreement. The application of prudential principles is a regulatory requirement. In every channeling of financing, BMT Daarut Tauhiid always uses the standard of assessment commonly used in the banking sector, namely 5 C, character, capacity, condition. capial and collateral. Aspects of 5 C are interrelated between one another can not stand alone. Therefore, by analyzing 5C accurately and thoroughly then the overall possibility of non-performing financing risks can be minimized. However, in its implementation BMT Daarut Tauhiid has a very high NPF Non Perfoming Finance level of up to 9%. This is because BMT Daarut Tauhiid which has a background boarding pesantren Daarut Tauhiid. So Its strongly influenced by the performance conditions of institutions or business entities in Daarut Tauhiid. While one of the financing partners of BMT Daarut Tauhiid are institutions or Business Entities in Pondok Pesantren Daarut Tauhiid.